Pravice in obveznosti delavcev in delodajalcev po noveli ZDR-1D - Senčur Peček, Darja (Podjetje in delo, 2024)
The article discusses the rights and obligations of employees and employers in connection with the conclusion of an employment contract, its termination, and during the duration of the employment contract, as derived from the amended and supplemented Employment Relationships Act (ZDR-1) after the entry into force of ZDR-1D amendment.
Keywords: amendment or conclusion of a new employment contract; carer’s leave; opozorilo; oskrbovalski dopust; pravica do odklopa; protection of workers who are victims of domestic violence; right to disconnect; sprememba ali sklenitev nove pogodbe o zaposlitvi; varstvo delavcev žrtev nasilja v družini; warning; ZDR-1D